Del gobierno democrático-representativo al gobierno de mera legitimación popular: breves consideraciones sobre las mutaciones de los regímenes - Bilancia, Francesco (2023)
In this article, the author asks what principle legitimizes power in contemporary democratic systems. The author discusses how the idea of democracy has been distorted. Democracy is unde rstood to be based solely on elections and on the popular consensus around the leader . This degenerates into a power that is highly concentrated, unstable, and volatile, which erodes the limits and controls imposed on political power. The author criticizes this position and defends the inseparable character of democracy and constitutionalism , taken as the most advanced legal way of basing a political regime on popular sovereignty, abiding by the limits and guarantees established by the constitution.